Clinical case: the effectiveness of metacognitive therapy in treating depression caused by emotional burnout in a healthcare worker during the war in Ukraine - Rusanov, Volodymyr (Psychosomatic Medicine and General Practice, 2024)
Introduction. Professional burnout is a critical issue among healthcare workers [1], particularly in the context of the war in Ukraine. Chronic stress, excessive workload, and the emotional toll of working with wounded soldiers and civilians contribute to a high risk of burnout, which often manifests similarly to depression [2]. The ongoing war has placed significant psychological strain on healthcare professionals, severely impacting their mental health. Currently, as part of the Solomiya project, Charité – Universitätsmedizin Berlin and the National Medical University named after O.O. Bohomolets are conducting an online training program aimed at preventing burnout among Ukrainian medical workers. This training focuses on reducing stress and preventing depression. The patient sought therapeutic assistance following the completion of this training, which became a pivotal moment in their decision to pursue individual psychotherapy. Objective. The purpose of this article is to demonstrate the effectiveness of short-term metacognitive therapy [3] in treating professional burnout and depressive disorders among healthcare workers. The clinical case presented in this article illustrates a doctor who experienced professional burnout amid the challenges of war, leading to a significant decline in quality of life. Materials and Methods. Patient S., a 40-year-old trauma surgeon, presented with symptoms of emotional burnout caused by the ongoing stress of working in wartime conditions. The patient reported feelings of exhaustion, loss of motivation, hopelessness, sleep disturbances, reduced productivity, and physical weakness. A course of metacognitive therapy was conducted, consisting of eight core and two booster sessions. Minimal pharmacotherapy was also employed, involving an anxiolytic as needed. Results. The treatment demonstrated positive outcomes, including a reduction in depression levels and improved control over negative thoughts. The patient reported decreased emotional exhaustion, renewed interest in professional activities, and a reduction in the adverse effects of stress on daily life. These findings highlight the value of metacognitive therapy as an effective approach for treating professional burnout among healthcare workers under extreme stress and suggest its potential as an essential component of national protocols for burnout prevention, especially in wartime conditions.